A Practical Fixed-Parameter Algorithm for Constructing Tree-Child Networks from Multiple Binary Trees - van Iersel, Leo; Janssen, Remie; Jones, Mark; Murakami, Yukihiro; Zeh, Norbert (Algorithmica, 2022)
We present the first fixed-parameter algorithm for constructing a tree-child phylogenetic network that displays an arbitrary number of binary input trees and has the minimum number of reticulations among all such networks. The algorithm uses the recently introduced framework of cherry picking sequences and runs in O ( ( 8 k ) k poly ( n , t ) ) time, where n is the number of leaves of every tree, t is the number of trees, and k is the reticulation number of the constructed network. Moreover, we provide an efficient parallel implementation of the algorithm and show that it can deal with up to 100 input trees on a standard desktop computer, thereby providing a major improvement over previous phylogenetic network construction methods.